2018
DOI: 10.1152/japplphysiol.00702.2017
|View full text |Cite
|
Sign up to set email alerts
|

Hip position and sex differences in motor unit firing patterns of the vastus medialis and vastus medialis oblique in healthy individuals

Abstract: Weakness of the vastus medialis oblique (VMO) has been proposed to explain the high prevalence of knee pain in female subjects. Clinicians commonly use exercises in an attempt to preferentially activate the VMO. Recently, our group found evidence to support clinical theory that the VMO is neurologically distinct from the vastus medialis (VM). However, the ability to voluntarily activate these muscle subsections is still disputed. The aim of this study was to determine if VM and VMO activation varies between se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 50 publications
(77 reference statements)
0
22
0
Order By: Relevance
“…In recent decades, vibrotactile noise stimulation has received attention as a possible intervention to improve somatosensory function and supplement postural control (Priplata et al, 2002;Galica et al, 2009;Magalhaes & Kohn, 2011;Lipsitz et al, 2015). Although the mechanism by which this intervention is effective is still uncertain, it has been theorized that mechanical noise stimulation elicits a stochastic resonance-like effect on the somatosensory system (Manjarrez et al, 2002;Collins et al, 2003;Moss & Milton, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent decades, vibrotactile noise stimulation has received attention as a possible intervention to improve somatosensory function and supplement postural control (Priplata et al, 2002;Galica et al, 2009;Magalhaes & Kohn, 2011;Lipsitz et al, 2015). Although the mechanism by which this intervention is effective is still uncertain, it has been theorized that mechanical noise stimulation elicits a stochastic resonance-like effect on the somatosensory system (Manjarrez et al, 2002;Collins et al, 2003;Moss & Milton, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the application of vibrotactile noise may sharpen one's control of body position by providing additional sensory information and increasing the body's ability to detect and respond to changes in body orientation. Vibratory noise stimulation has shown to be effective in reducing postural sway among healthy young subjects as well as elderly subjects and patients with degraded somatosensory function due to diabetes and stroke (Collins et al, 2003;Priplata et al, 2002Priplata et al, & 2006Magalhaes & Kohn, 2011). Additional work has demonstrated that postural sway may also be improved with other modes of noise stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Garrick et al believed that strengthening of the vastus medialis is an important goal in the treatment of anterior knee pain [12]. The vastus medialis and the vastus medialis oblique can be activated differentially and their motor unit recruitment properties are affected by sex and hip position [13]. The appropriate treatment for this syndrome is still unknown, but the most commonly accepted therapeutic intervention is exercise therapy [12,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%